["The New View of Investment"]: Reply - Phelps, E. S.; Yaari, M. E. (Quarterly Journal of Economics, 1964)
Journal Article “The New View of Investment”: Reply Get access E. S. Phelps, E. S. Phelps Yale University Search for other works by this author on: Oxford Academic Google Scholar M. E. Yaari M. E. Yaari Yale University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 78, Issue 1, February 1964, Pages 172–176, https://doi.org/10.2307/1880553 Published: 01 February 1964